Preparation of pigmentary grade bismuth vanadate Bi4V2O11 via coprecipitation method - Wendusu; Moxiye (Journal of Asian Ceramic Societies)
In this study, Bi4V2O11 pigments were synthesized using a coprecipitation method, and the pH value and calcination temperature were optimized from the viewpoint of red colorant. The obtained samples were characterized by XRF, XRD, Rietveld refinement, TEM, UV–vis diffuse reflectance spectrometry, SEM, XPS and color measurements. It was found that Bi4V2O11 samples with single-phase monoclinic structure could be prepared, when the calcination temperatures were 973 and 1073 K. The obtained single-phase Bi4V2O11 samples exhibited reddish hue. For the sample, which was prepared at pH = 7.0 and calcined at 973 K, its color coordinates were L* = 46.41, a* =  +27.41, b* =  +26.09.